Der gerettete Retter Exodus 1-2 in patristischer und rabbinischer Interpretation - Siquans, Agnethe 1971-; Vandenhoeck & Ruprecht ([Erscheinungsort nicht ermittelbar] Verlag der Österreichischen Akademie der Wissenschaften, 2021)
The book deals with patristic and rabbinic interpretations of the birth story of Moses in Exodus 1-2. The Christian and Jewish exegetes of late antiquity interpreted the text as part of their Bible, in dialogue with each other and in dissociation from each other
Das Buch befasst sich mit patristischen und rabbinischen Interpretationen der Geburtsgeschichte des Mose in Exodus 1-2. Die christlichen und jüdischen Ausleger der Spätantike deuteten den Text als Teil ihrer Bibel, in Dialog miteinander und Abgrenzung voneinander
German
Keywords: Old Testaments; Biblical studies & exegesis; Judaism: sacred texts; Exodus; Moses; patristic Bible interpretation; rabbinic Bible interpretation; Christian-Jewish dialogue; ÖFOS 2012, Old Testament studies; ÖFOS 2012, Patrology; ÖFOS 2012, Jewish religion; Exodus; Mose; patristische Bibelauslegung; rabbinische Bibelauslegung; christlich-jüdischer Dialog; ÖFOS 2012, Alttestamentliche Bibelwissenschaft; ÖFOS 2012, Patrologie; ÖFOS 2012, Jüdische Religion